Cluster headache: an update on clinical features, epidemiology, pathophysiology, diagnosis, and treatment - San-Juan, Daniel; Velez-Jimenez, Karina; Hoffmann, Jan; Martínez-Mayorga, Adriana Patricia; Melo-Carrillo, Agustín; Rodríguez-Leyva, Ildefonso; García, Silvia; Collado-Ortiz, Miguel Ángel; Chiquete, Erwin; Gudiño-Castelazo, Manuel; Juárez-Jimenez, Humberto; Martínez-Gurrola, Marco; et al. (Frontiers in Pain Research, 2024)
Cluster headache (CH) is one of the worst primary headaches that remain underdiagnosed and inappropriately treated. There are recent advances in the understanding of this disease and available treatments. This paper aims to review CH's recent clinical and pathophysiological findings, diagnosis, and treatment. We performed a narrative literature review on the socio-demographics, clinical presentations, pathophysiological findings, and diagnosis and treatment of CH.CH affects 0.1% of the population with an incidence of 2.07-9.8/100,00 person-yearshabitants, a mean prevalence of 53/100,000 inhabitants (3-150/100,000 inhabitants).The male-to-female ratio remains inconclusive, as the ratio of 4.3:1 has recently been modified to 1.3-2.6, possibly due to previous misdiagnosis in women. Episodic presentation is the most frequent (80%). It is a polygenetic and multifactorial entity that involves dysfunction of the trigeminovascular system, the trigeminal autonomic reflex, and the hypothalamic networks. An MRI of the brain is mandatory to exclude secondary etiologies. There are effective and safe pharmacological treatments, oxygen, sphenopalatine, and great occipital nerve block, with the heterogeneity of clinical trial designs for patients with CH divided into acute, transitional, or bridge treatment (prednisone) and preventive interventions.In conclusion, CH remains underdiagnosed, mainly due to a lack of awareness within the medical community, frequently causing a long delay in reaching a final diagnosis.Recent advances in understanding the principal risk factors and underlying pathophysiology exist. There are new therapeutic possibilities that are effective for CH. Indeed, a better understanding of this challenging pathology will continue to be a subject of research, study, and discoveries in its diagnostic and therapeutic approach.